AODTH-004 Intestinal epithelial-mesenchymal signalling pathways in homeostasis and inflammation. (17th June 2017) - Biswas, S; Davis, H; Leedham, S
Abstract : Introduction: Polarised intercompartmental morphogen gradients regulate epithelial cell fate determination. Wnt activity is highest at the crypt base promoting stem-cell stemness and transit-amplifying cell proliferation whereas BMP and Hedgehog (HH) are high at the luminal surface promoting differentiation. Inflammation induces transient, regulated instability in mucosal signalling gradients. We hypothesise that this promotes stem/progenitor behaviour in epithelial cells as part of a physiological adaptive cell reprogramming response to effect epithelial restitution in ulcer healing. Method: Individual colonic crypts from healthy and inflamed patients were microdissected into crypt tops, crypt bases and mesenchyme. Illumina microarrays were used to find genes differentially expressed between compartments, and results validated by qPCR. Stromal signalling variation between the muscularis and intercrypt mesenchyme was assessed by laser dissection and RNASeq. Next regulation of BMP by the Hedgehog pathway was assessed. Fibroblasts were cultured from normal patient biopsies and exposed to HH inhibitor cyclopamine. Morphogen disruption was assessed in a mouse model of colitis, and following transgenic epithelial deletion of HH ligand. Results: There were anticipated expression gradients of Wnt and BMP target genes between epithelial tissue compartments but this was not mirrored by endogenous ligand and receptor expression. In colitis, gene set enrichment analysis showed enhanced transit amplifying cell signatures at the crypt base and reduced DNA damage response genes at the crypt top. In homeostasis 1529 genes were differentially expressed between spatially distinct stromal regions intimating mesenchymal functional heterogeneity. In DSS colitis GREM1 expression was massively increased in muscularis layers and ulcer beds. In the Ah-Cre; IHH fl/fl mouse there was a similar GREM1 response, suggesting control of the BMP pathway by HH. Likewise addition of cyclopamine to fibroblast culture led to increased GREM1 by qPCR. Conclusion: Disparity between target gene expression and epithelial ligand/receptor expression suggests receptor-independent control from intercompartmentally expressed molecules regulates signalling gradients. Strictly regulated Wnt, BMP and HH gradients are dysregulated in colitis, skewing crypt basal cell fate towards proliferation and impairing differentiated cell DNA damage response. In homeostasis epithelial Hedgehog signalling maintains a BMP ligand active fibroblast population and restricts GREM1 expression to the subcrypt stroma. In inflammation epithelial denudation leads to reduced IHH signalling, reducing BMP activity and promoting surrounding crypt fission to aid tissue restitution. This work highlights the importance of the microenvironment in regulating epithelial cell fate determination in health and disease. Disclosure of Interest: None Declared